2008
DOI: 10.1371/journal.pbio.0060100
|View full text |Cite
|
Sign up to set email alerts
|

Host PrP Glycosylation: A Major Factor Determining the Outcome of Prion Infection

Abstract: The expression of the prion protein (PrP) is essential for transmissible spongiform encephalopathy (TSE) or prion diseases to occur, but the underlying mechanism of infection remains unresolved. To address the hypothesis that glycosylation of host PrP is a major factor influencing TSE infection, we have inoculated gene-targeted transgenic mice that have restricted N-linked glycosylation of PrP with three TSE strains. We have uniquely demonstrated that mice expressing only unglycosylated PrP can sustain a TSE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
109
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 35 publications
(48 reference statements)
14
109
1
2
Order By: Relevance
“…However, conversion is not observed in transgenic mice expressing unglycosylated PrP, indicating important differences in the behavior of the protein in vivo. Although recent results demonstrate that prion transmission can take place regardless of PrP glycosylation (40), it seems to be important for the transmission of certain strains (41). Thus, mono-and unglycosylated PrP seem to be better substrates for conversion than diglycosylated PrP.…”
Section: Discussionmentioning
confidence: 94%
“…However, conversion is not observed in transgenic mice expressing unglycosylated PrP, indicating important differences in the behavior of the protein in vivo. Although recent results demonstrate that prion transmission can take place regardless of PrP glycosylation (40), it seems to be important for the transmission of certain strains (41). Thus, mono-and unglycosylated PrP seem to be better substrates for conversion than diglycosylated PrP.…”
Section: Discussionmentioning
confidence: 94%
“…Again the alterations observed via the intraperitoneal route would at best argue for the peripheral nerves being only a minor component of the route to the CNS. We have established in parallel studies that while mice expressing only unglycosylated PrP can become infected with a TSE agent following intracerebral challenge (Tuzi et al, 2008), they are not capable of TSE neuroinvasion following peripheral routes of inoculation (EC, BMB and JCM unpublished data) thus implicating glycosylated PrP as important in the peripheral phases of infection (replication and/or transport). It may be the case that fully glycosylated PrP is a requirement for agent replication in the periphery but is not a requirement for agent transport, or vice versa.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, different ratios of PrP C glycoforms are found in different brain regions (2,10,32), and different prion strains produce distinctive ratios of PrP Sc glycoforms upon serial passage (9). Studies of transgenic mice show that PrP C glycosylation influences patterns of prion neurotropism in a strain-dependent manner (11,35). Studies with human brain specimens have shown that the regional distribution of PrP Sc glycoforms is heterogenous in the sporadic but not the variant form of Creutzfeldt-Jakob disease (21).…”
mentioning
confidence: 99%